2014
DOI: 10.1152/jn.00486.2013
|View full text |Cite
|
Sign up to set email alerts
|

Learning the spatial features of a locomotor task is slowed after stroke

Abstract: Tyrell CM, Helm E, Reisman DS. Learning the spatial features of a locomotor task is slowed after stroke. J Neurophysiol 112: 480 -489, 2014. First published April 30, 2014 doi:10.1152/jn.00486.2013The capacity for humans to learn a new walking pattern has been explored with a split-belt treadmill during single sessions of adaptation, but the split-belt treadmill can also be used to study longer-term motor learning. Although the literature provides some information about motor learning after stroke, existing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
88
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(94 citation statements)
references
References 48 publications
3
88
2
1
Order By: Relevance
“…Spatial and temporal parameters of gait have been found to respond differently during split-belt walking (Malone & Bastian, 2010; Malone, Vasudevan, & Bastian, 2011; Tyrell, Helm, & Reisman, 2014). Therefore, both spatial (step length) and temporal (limb phasing) variables were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial and temporal parameters of gait have been found to respond differently during split-belt walking (Malone & Bastian, 2010; Malone, Vasudevan, & Bastian, 2011; Tyrell, Helm, & Reisman, 2014). Therefore, both spatial (step length) and temporal (limb phasing) variables were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Step length was labeled as Left or Right based on leading leg. Stride by stride symmetry data for step length was calculated as: false(boldnormalStep boldnormalLength boldnormalof boldnormalLeg boldnormalon boldnormalSlow boldnormalBeltboldnormalSymmetrical boldnormalStep boldnormalLengthfalse)boldnormalSymmetrical boldnormalStep boldnormalLengthWhere symmetrical step length = (Left step length + Right step length)/2 (Tyrell et al, 2014; Tyrell, Helm, & Reisman, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that spatial and temporal variables respond differently to split-belt walking (Malone and Bastian, 2010; Malone et al, 2011; Malone et al, 2012a; Tyrell et al, 2014). We therefore evaluated a spatial (step length) and temporal (limb phasing) variable in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Limb phase was a measure of the time lag between contralateral peak flexion and ipsilateral peak extension, and was calculated as described in our previous work (Tyrell et al, 2014). In order to evaluate the specific characteristics of adaptation in our participants, we calculated the following measures for each variable (Malone et al, 2011):…”
Section: Methodsmentioning
confidence: 99%
“…The time course of this adaptation process has been studied in detail in recent years (Bruijn et al 2012;Finley et al 2014;Malone and Bastian 2010;Tyrell et al 2014;Vasudevan et al 2011). Using a split-belt condition, the Bastian group found that intralimb parameters (such as limb excursion; i.e., the distance the foot travels along the belt during the stance phase, previously termed stride length; Hoogkamer et al 2014a) adjust rapidly and thus can be considered as feedback-controlled parameters (rather than feedforward; Morton and Bastian 2006;Reisman et al 2005).…”
mentioning
confidence: 99%